1984
DOI: 10.1038/icb.1984.20
|View full text |Cite
|
Sign up to set email alerts
|

Organotin Implications in Anticarcinogenesis. Background and Thymus Involvement

Abstract: Summary, A comprehensive study of the scientific literature regarding tin content in normal and pathogenii; himiiin tissue has disclosed that various organotin materials retard both the onset and growth of cancer in laboratory animals, and decreased tissue tin in humans may be associated with lumour development.Initial studies by the authors have shown that the thymus gland of the mouse possesses a relatively high concentr;ition of tin and is also the major site of accumulation for I'C-labelied tri-n-biityltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…During the last two decades, they have caught much attention for their potential biocidal activities and, in recent years, several organotin compounds have been synthesized, some with interesting in vitro cytotoxic activity [17]. Such activity, often revealed higher than that of cisplatin and sometimes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, they have caught much attention for their potential biocidal activities and, in recent years, several organotin compounds have been synthesized, some with interesting in vitro cytotoxic activity [17]. Such activity, often revealed higher than that of cisplatin and sometimes …”
Section: Discussionmentioning
confidence: 99%
“…A huge number of tin derivatives have been prepared and tested in the past as possible antitumor agents [17][18][19] and many of them exhibited interesting activity in specific cancer models, but they lacked activity against a broad spectrum of experimental tumors [1].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in (1). whose molecular structure is already known (Bohra et al, 1994;Selvaraju et al, 1994), is due to its antitumor activity (Smith, 1978;, Cardarelli & Libby, 1984. Then, during reactivity studies of (1) with 2-thiouracil [which exhibits a marked affinity for melanin-producing tissue (W~itjen et al, 1982)], we unexpectedly obtained white crystals of the title compound, (2), identified as methanediyl bis(N,N'-diethyldithiocarbamate) by X-ray structure and IR spectroscopic analysis.…”
Section: Commentmentioning
confidence: 99%